Tool wear characteristics of cutting and extrusion processing technology based on the edge-chipping effect. Issue 2 (14th March 2016) - Tian, Xinli; Wang, Long; Wang, Wanglong; Li, Yongdong; Ji, Kaiwen
Abstract : Purpose: – The cutting and extruding processing technology for ceramics based on the edge-chipping effect is a new contact removal machining method for hard, brittle materials such as engineering ceramics. This paper aims to provide an important reference to understand the tool wear mechanism and the wear law of this new processing technology. Design/methodology/approach: – The real-time temperature monitoring and the observation of micro-morphology are used to analyse the wear characteristics of the tool face. In addition, the research focuses on the influence of three processing parameters (axial feed rate, thickness of flange and depth of groove) on characteristics including tool wear. Findings: – The temperature variation shows that the new processing technology improves the tool temperatures condition. The tool is worn mainly by mechanical friction including abrasive wear, and the flank face also suffers the sustained scratching of residual materials on the rough machining surface. With increased feed rate, the wear of the rear face of the major flank initially decreased and then increased. As the depth of the retained flange increases, the wear became worse. The wear initially decreased and then increased with increasing depth of groove. Research limitations/implications: – Study on the new processing technology is still in its early stages. Therefore, researchers are encouraged to test the proposed propositions further. Practical implications: – The machining process itself destroys materials, albeit a controllable manner: based on this principle, the authors proposed a new machining technology based on cracks driven by edge chipping. In this way, the surface of such ceramics is removed. Therefore, the research provides a new method for reducing processing costs and promoting the extensive application of engineering ceramic materials. Originality/value: – The cutting and extruding processing technology based on cracks driven by edge-chipping effect makes full use of the stress concentration effect caused by prefabricated defects, and the edge-chipping effect which occurs during machining-induced crack propagation. The wear mechanism and law of its tool is unique than other machining ways. This paper provides an important reference to understand the tool wear mechanism and the machining mechanism of this new processing technology. With the application of this study, the ceramics could be removed with less energy consumption and the tools with the hardness of lower than its own one. Therefore, it could not only reduce the processing costs but also promote the extensive applications of engineering ceramic materials.